Income Analysis Of Palm Sugar Craftsmen In The Village Of Water Meles Atas Selupu Rejang District Rejang Lebong Regency - Darwan Effendi; Indah Fitria (UNIVED Press, Dehasen University Bengkulu, 2022)
Aren (Arenga pinnata Merr) is a type of palm that has a high economic value, its spread is very wide in Indonesia. All parts of the palm plant, from leaves to roots, can be utilized. The main product of palm sugar is sap. Sap is a liquid that is tapped from the male flower of the palm tree, which is nothing but the metabolism of the tree. This liquid called palm juice contains between 10-15% sugar. Superior palm products as a source of food and energy include palm sugar, ant sugar, fresh roomie, fro, and alcoholic drinks. Besides palm products are widely used for craft materials, as well as building materials. In terms of its economy, the business of making palm sugar can increase income and improve the family's standard of living. This can occur if the income earned by palm sugar craftsmen is greater than the costs incurred. The amount of income that will be obtained from a business activity depends on several factors that influence it such as how much land is owned, how the level of production, who is the identity of the entrepreneur, and how much labor is used. In conducting this palm sugar business, the craftsman hopes to increase his income so that his daily needs can be met.